Increased Lamin B1 Levels Promote Cell Migration by Altering Perinuclear Actin Organization - Andrea Fracchia; Tal Asraf; Mali Salmon-Divon; Gabi Gerlitz (Cells, 2020)
Cell migration requires reposition and reshaping of the cell nucleus. The nuclear lamina is highly important for migration of both primary and cancer cells. B-type lamins are important for proper migration of epicardial cells and neurons and increased lamin B to lamin A ratio accelerates cancer cell migration through confined spaces. Moreover, a positive association between lamin B1 levels and tumor formation and progression is found in various cancer types. Still, the molecular mechanism by which B-type lamins promote cell migration is not fully understood. To better understand this mechanism, we tested the effects of lamin B1 on perinuclear actin organization. Here we show that induction of melanoma cell migration leads to the formation of a cytosolic Linker of Nucleoskeleton and Cytoskeleton (LINC) complex-independent perinuclear actin rim, which has not been detected in migrating cells, yet. Significantly, increasing the levels of lamin B1 but not the levels of lamin A prevented perinuclear actin rim formation while accelerated the cellular migration rate. To interfere with the perinuclear actin rim, we generated a chimeric protein that is localized to the outer nuclear membrane and cleaves perinuclear actin filaments in a specific manner without disrupting other cytosolic actin filaments. Using this tool, we found that disruption of the perinuclear actin rim accelerated the cellular migration rate in a similar manner to lamin B1 over-expression. Taken together, our results suggest that increased lamin B1 levels can accelerate cell migration by inhibiting the association of the nuclear envelope with actin filaments that may reduce nuclear movement and deformability.